The effect of musa acuminata stem in increasing macrophage and neovascular cells of healing process - Apriasari, Maharani Laillyza; Puspitasari, Dewi; Rahayu, Retno Pudji; Ernawati, Diah Savitri (Universitas Padjadjaran, 2018)
Introduction: Musa acuminata stem has both of imunostimulatory and imunosuppressant effects that are influenced by their concentrations. The study aimed to analyze the effect of Mauli banana stem extract (EMBS) to increase the number of macrophage and neovascular cells in traumatic ulcer healing. Methods: Rattus norvegicus of male Wistar strain were used as model of traumatic ulcer. The left buccal mucous was biopsied, then used the histopathology method to find the number of macrophage and neovascular cells. Results: EMBS gel was effected when administered at a concentration of 37.5% because it significantly increased the number of macrophage and neovascular cells in traumatic ulcer healing on the 3rd day to 5th days. Conclusion: It can be concluded that EMBS within concentration of 37.5% can accelerate ulcer healing through the increasing number of macrophage and neovascular cells.